Pengaruh Pengeluaran Riset dan Inovasi, Total Direct Investment, dan Indeks Pembangunan Manusia Terhadap Penggunaan Energi Terbarukan di Indonesia - Muhammad Dicky Dermawan; Muzdalifah (PPJP ULM, 2026)
Indonesia is a developing country with vast renewable energy potential, yet its utilization remains far from optimal, contributing only 12.3% to the national energy mix in 2022. Factors such as research and innovation expenditure, investment, and human development quality are believed to influence this transition. Therefore, this study aims to analyze the effect of Research and Innovation Expenditure, Total Direct Investment (TDI), and Human Development Index (HDI) on the use of renewable energy in Indonesia. The research method employed in this study is a quantitative approach using multiple linear regression (OLS). The data used are annual secondary time-series data obtained from Statistics Indonesia (BPS), the World Bank, the National Research and Innovation Agency (BRIN), and the Ministry of Energy and Mineral Resources, covering 8 observations for the period 2015–2022. Classical assumption tests were conducted, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results indicate that, simultaneously, all three variables have a significant effect on renewable energy use. However, partially, only the Human Development Index has a positive and significant effect, while research and innovation expenditure and TDI do not show significant effects. These findings suggest that improving the quality of human resources plays a crucial role in promoting the adoption of clean energy, whereas the contributions of research and investment still need to be enhanced to more effectively support the energy transition.